Penanaman Nilai-Nilai Karakter Religius Siswa Dalam Pembelajaran Sejarah Kebudayaan Islam - Sulaiman, Husnan; Ameliani, Rahmatika (STAI Al-Musaddadiyah Garut, 2023)
This study is motivated by the researcher's concern about the low levels of religious attitudes among students in schools, influenced by the negative impact of foreign cultures on the development of students' religious character. Therefore, there is a need to strengthen students' character within the process of Islamic Cultural History (SKI) learning. The aims of this research are to describe the inculcation of religious character values in students, the teaching of Islamic Cultural History, and the supporting and inhibiting factors in instilling religious character values in SKI learning for 11th-grade students at MAN 1 Garut. This study employs a field research approach with a qualitative methodology, using descriptive analytical methods. Data collection techniques include observation, interviews, and document analysis involving the school principal, SKI teachers, and 11th-grade students at MAN 1 Garut. Data analysis involves data reduction, data presentation, and drawing conclusions. The findings indicate that the inculcation of religious character values in Islamic Cultural History learning is achieved through habitual practices, starting lessons with prayers and Quranic recitations, and the method of exemplification by emulating the characters of historical figures. Supporting factors include supervision of learning activities, exemplary behavior from teachers, the principal, parents, the curriculum, and the willingness of students to learn Islamic Cultural History. Inhibiting factors come from two sources: internal factors, such as student laziness, sleepiness, and misuse of mobile phones, and external factors, including family issues (lack of parental attention) and the school environment (peer influence). Keywords: Inculcation of Religious Character Values, Islamic Cultural History Learning